Epidemiology in the Era of Health Informatics: Opportunities & Challenges - Kumar, Rajesh (Indian Journal of Community Health, 2016)
Over the years, epidemiology has played a key role in improving our understanding about the determinants of health and disease. In the 19th century epidemiological observations led to the discovery of the modes of communication of cholera much before the discovery of the causative organism responsible for it. Similarly, in the 20th century, it led to the discovery of the risks of tobacco smoking, and the modes of transmission of AIDS. In the 21st century, advancement in the computation, visualization, communication, and mhealth technologies are likely to expand the landscape of epidemiology which has now acquired the status of a core discipline of health sciences.